A Framework For Boosting Revenue Generation From Land Taxes in Ogun State, Nigeria - Atinuke Adibempe Orekan (Ilomata International Journal of Tax and Accounting, 2023)
The study developed a framework for boosting revenue generation from land taxes in Ogun State Nigeria. The choice of Ogun state was hinged on the fact that it is both an economically and an industrial state. It exhibits the dynamism of land activities traceable to land taxation. Data were collected through a well-structured questionnaire, personal interviews and review of government documents were also conducted. Questionnaires were administered to the 23 top management staff at the Board of Internal Revenue Services in Ogun State. Personal interviews were also conducted. Using the frequency table and SPSS to analyse, the result revealed that government does not have enough information on property, property owners and property transactions. These which affected the revenue from land taxed to fall-short. In conclusion, land titling should be made compulsory and at the same time be flexible, so that government can have access to property information which will in turn improve revenue mobilisation for the state government.